Analisis Pengaruh Sektor Pariwisata Terhadap PAD di Kabupaten Mojokerto dan Kabupaten Pasuruan - Nakrowiyah, Finda Rohmatin; Imaningsih, Niniek (Gorontalo State University, 2026)
Tourism is the main sector in increasing local revenue. Tourism is being developed by many countries in the world, including Indonesia as a foreign exchange earner. The tourism sector plays an important role in increasing Regional Original Income, especially in tourist areas. This research aims to analyze the influence of the sector on the number of tourist visits, number of hotel rooms and number of restaurants on Regional Original Income. The data used in this research is secondary data for the years 2008-2022. The method used in this research is multiple linear regression analysis using Eviews 12 software. The results of the research show that the number of tourist visits has a negative and insignificant effect on PAD in Mojokerto Regency, but has a positive and significant effect on PAD in Pasuruan Regency. The variable number of hotel rooms has a positive and significant effect on PAD in Mojokerto Regency and Pasuruan Regency. The variable number of restaurants has a negative and significant effect on PAD in Mojokerto Regency, but has a negative and insignificant effect on PAD in Pasuruan Regency.